Analysis of Road Service Levels on Standard and Non-Standard Road on Bantul Road Km 6.5 – Km 8 Using the 2023 Indonesian Road Capacity Guidelines - Nur Budi Susanto; Wiryanta; Irvan Adji Prayitno (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
Bantul is a regency in the Special Region of Yogyakarta Province with a motor vehicle growth rate that exceeds the population growth rate. The Bantul Road is a national road connecting Yogyakarta - Bantul city border with the function of primary collector road one. However, in the implementation of preservation in 2022, at Km 6.5 - Km 7.5 a permanent median was added as a lane separator without any widening of the road that is not referenced in the Road Geometric Design Guidelines, the 1997 Indonesian Road Capacity Manual (MKJI), or the 2023 Indonesian Road Capacity Guidelines (PKJI). Therefore, this study aims to analyze the level of service of the Bantul Road, especially at Km 6.5 - Km 7.5 which is affected by preservation in 2022 and Km 7.5 - Km 8 which is a 4-lane 2-way road that is in accordance with regulations as input and evaluation for policy makers. The research method used was a traffic counting survey to then analyze the level of road service based on PKJI 2023. The results of the analysis show that in general, the Bantul Road Km 6.5 - 7.5 which is not standard has the degree of saturation 0.88 that exceeds the standar degree of saturation of a 0.85 and a level of service D/E, so that it remains not optimal. To improve the service level to at least D across the entire coridor, it is proposed to widening the non standard segment to a standard 4/2-D road with 3,5 m width each lane. However, this necessitates significant land acquisition, presenting substantial financial, legal, and socio-economic barriers that require transparent governance and proactive stakeholder engagement for successful implementation.